61.3k views
4 votes
Can somebody divide this : (4x^5 – 3x^3 + 2x – 1) / ( x^2 – 2x )

User Yakov
by
6.0k points

1 Answer

5 votes


4x^5=x^2\cdot4x^3, and
4x^3(x^2-2x)=4x^5-8x^4. Subtract this from
4x^5-3x^3+2x-1 to get a remainder of


(4x^5-3x^3+2x-1)-(4x^5-8x^4)=8x^4-3x^3+2x-1


8x^4=x^2\cdot8x^2, and
8x^2(x^2-2x)=8x^4-16x^3. Subtract this from the previous remainder to get a new remainder of


(8x^4-3x^3+2x-1)-(8x^4-16x^3)=13x^3+2x-1


13x^3=x^2\cdot13x, and
13x(x^2-2x)=13x^3-26x^2. Subtract this from the previous remainder to get a new remainder of


(13x^3+2x-1)-(13x^3-26x^2)=26x^2+2x-1


26x^2=x^2\cdot26, and
26(x^2-2x)=26x^2-52x. Subtract this from the previous remainder to get a new remainder of


(26x^2+2x-1)-(26x^2-52x)=54x-1


x^2 does not divide
54x, so we're done, and we've found that


(4x^5-3x^3+2x-1)/(x^2-2x)=4x^3+(8x^4-3x^3+2x-1)/(x^2-2x)


(4x^5-3x^3+2x-1)/(x^2-2x)=4x^3+8x^2+(13x^3+2x-1)/(x^2-2x)


(4x^5-3x^3+2x-1)/(x^2-2x)=4x^3+8x^2+13x+(26x^2+2x-1)/(x^2-2x)


(4x^5-3x^3+2x-1)/(x^2-2x)=\boxed{4x^3+8x^2+13x+26+(54x-1)/(x^2-2x)}

User Tomas Kirda
by
5.6k points